2019
DOI: 10.1111/pbi.13276
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene‐responsive factor 4 is associated with the desirable rind hardness trait conferring cracking resistance in fresh fruits of watermelon

Abstract: Summary Fruit rind plays a pivotal role in alleviating water loss and disease and particularly in cracking resistance as well as the transportability, storability and shelf‐life quality of the fruit. High susceptibility to cracking due to low rind hardness is largely responsible for severe annual yield losses of fresh fruits such as watermelon in the field and during the postharvest process. However, the candidate gene controlling the rind hardness phenotype remains unclear to date. Herein, we report, for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 50 publications
2
53
0
Order By: Relevance
“…Liao's research strongly supported Ethylene-responsive factor 4 (ERF4) was associated with rind hardness and cracking resistance in watermelon fruits [88]. In our study, DEGs also included ethylene, as well as cell wall and redox related genes.…”
Section: Lncrnas Regulate Tomato Fruit Cracking By Coordinating Gene supporting
confidence: 70%
“…Liao's research strongly supported Ethylene-responsive factor 4 (ERF4) was associated with rind hardness and cracking resistance in watermelon fruits [88]. In our study, DEGs also included ethylene, as well as cell wall and redox related genes.…”
Section: Lncrnas Regulate Tomato Fruit Cracking By Coordinating Gene supporting
confidence: 70%
“…For example, for XLOC_033910 (Fig. 6c) Liao's research strongly supported Ethylene-responsive factor 4 (ERF4) was associated with rind hardness and cracking resistance in watermelon fruits [89]. In our study, DEGs also included ethylene, as well as cell wall and redox related genes.…”
Section: Lncrnas Regulate Tomato Fruit Cracking By Coordinating Gene supporting
confidence: 75%
“…Similarly, the knockdown of SlDCR resulted in the disrupted epidermal layer of tomato with changes of lignin, suberin, phenylpropanoids and fatty acids [ 12 , 13 ]. Many investigations indicated that polyphenolic exhibited important roles in regulating fruit skin cracking and ensuring superior quality and freshness [ 12 , 14 ]. Vulavala et al revealed that lignin and suberin are involved in potato periderm formation and maturation, and that the phellogen may affect the incomplete skin-set and skin injuries [ 15 ].…”
Section: Introductionmentioning
confidence: 99%